Representasi Objek Magis dalam Budaya Jawa: Kosakata, Ikon, dan Mitos - Sunarya Sunarya; Rawinda Fitrotul Mualafina; Raden Yusuf Sidiq Budiawan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study aims to reveal the vocabulary used in naming magical objects in Javanese society as icons that carry connotative meanings related to myths. The Javanese believe in various types of magical objects, such as stones, metals, as well as parts of plants and animals, which function as markers. Each vocabulary referring to these objects forms an icon with specific meanings according to their magical attributes. This research employs a qualitative approach with Barthes’ semiotic analysis, encompassing three levels of meaning: denotative, connotative, and mythological. Data were collected through interviews, recordings, observations, and note-taking with seven informants—five from the general community and two knowledgeable about primbon and Javanese mysticism—as well as written sources from Primbon texts. The findings indicate that at the denotative level, the vocabulary of magical objects represents the literal meaning of the objects. At the connotative level, the objects carry unique characteristics such as shape, color, sound, or specific traits that draw attention. Meanwhile, at the mythological level, the vocabulary of magical objects is understood as a symbolic expression of Javanese beliefs, which are thought to possess supernatural power and magical functions for their owners.